IMPROVING THE AUTHORITY OF THE REGIONAL REPRESENTATIVE COUNCILS IN THE STATE GAZETTE OF THE REPUBLIC OF INDONESIA ACCORDING TO THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Dadang Gandhi (Jurnal Hukum Replik, 2020)
The existence of the Regional Representative Council (DPD) which is regulated in Article 22D of the 1945 Constitution of the Republic of Indonesia (UUDNRI of 1945) with the authority of the DPD as regulated in Law Number 2 of 2018 concerning the Second Amendment to Law Number 17 of 2014 Regarding the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council (MD3), in particular Article 249 Paragraph (1) letter e. Article 22D of the 1945 Constitution places the position of the DPD as an institution that has the authority to submit a Bill relating to regional autonomy, central and regional relations, the formation and expansion of regions and the merger of regions, management of natural resources and other economic resources as well as related also by placing the DPD position to monitor and evaluate the Draft District / City Regional Regulations and Regency / City Regional Regulations according to Law Number 2 of 2018 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Regional People's Representative Council (DPR) ( MD3). This authority will cause problems especially those regulated in Law Number 2 of 2018 concerning MD3, because the Regency / City Regional People's Representative Council and the Governor as representatives of the central government do the same thing as is done by the DPD as regulated in Law Number 23 2014 concerning Regional Government, particularly in the provisions of Article 149 Paragraph (1) and Article 153 Paragraph (1). While the form of coordination that will be carried out by the DPD and the Regional Government has yet to exist, in addition to the DPD's position as a high state institution will cause problems when coordinating with the Regency / City DPRD as an element of the regional government.Keywords: The telescope, Position, DPD, State Administration, Republic of Indonesia